2017
DOI: 10.1002/2017tc004531
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircons from the Nanaimo basin, Vancouver Island, British Columbia: An independent test of Late Cretaceous to Cenozoic northward translation

Abstract: The development of the Cordilleran orogen of western North American is disputed despite a century of study. Paleomagnetic observations require large‐scale dextral displacements of crustal fragments along the western margin of North America, from low latitudes to moderate latitudes during the Cretaceous‐Paleogene. A lack of corroborating geological evidence for large‐scale (>1500 km) displacements has prevented the widespread integration of paleomagnetic data into most contemporary tectonic models for the margi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 160 publications
(219 reference statements)
3
51
1
Order By: Relevance
“…In this study, we use detrital zircon dates first reported by Matthews et al (2017) to constrain the age of Nanaimo Group deposits on Hornby and Denman Islands. Dates for 300 zircons per sample were acquired via laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) techniques (Matthews and Guest, 2016) and were previously used by Englert et al (2018) to determine that Geoffrey Formation channel deposits on Hornby Island spanned 72.8 ± 1.2 Ma to 71.2 ± 1.0 Ma.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we use detrital zircon dates first reported by Matthews et al (2017) to constrain the age of Nanaimo Group deposits on Hornby and Denman Islands. Dates for 300 zircons per sample were acquired via laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) techniques (Matthews and Guest, 2016) and were previously used by Englert et al (2018) to determine that Geoffrey Formation channel deposits on Hornby Island spanned 72.8 ± 1.2 Ma to 71.2 ± 1.0 Ma.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Building on that work here, we calculate MDAs and uncertainties for 12 samples on Hornby and Denman Islands by taking a weighted mean of zircon dates from the youngest grain cluster, defined as three or more grains with overlapping dates at 2σ uncertainty (YC2σ) (Dickinson and Gehrels, 2009; see Supplemental Files S1-S3 1 for acquisition parameters, details of the uncertainty propagation, complete data sets, and MDA weighted-average graphs). This is a conservative method, shown to produce an MDA younger than the true depositional age of the sample <0.5% of the time Detrital zircon sample location (Matthews et al, 2017) Paleomagnetic sample location (Enkin et al, 2001 ) Approximate foram sample location (Sliter, 1973) Approximate ammonite sample location (Muller and Jeletzky, 1970 Research Paper (Coutts et al, 2019). These new ages are integrated with previously published paleontological and paleomagnetic data sets to temporally constrain the timing of deposition within the channel-system succession.…”
Section: ■ Methodsmentioning
confidence: 99%
“…It overlaps, however, with ca. 75 Ma detrital zircon age peaks documented for the Maastrichtian strata of the Nanaimo Basin, suggesting a possible source for the Nanaimo grains (Englert et al, 2018;Matthews et al, 2017). Late Cretaceous-Paleogene time is marked by a change to dextral transpression in the CMB, as indicated by dextral motion on faults both within and adjacent to the Coast Mountains (e.g., Hollister & Andronicos, 2006;Rusmore et al, 2001;Umhoefer & Schiarizza, 1996).…”
Section: 1029/2018gc007874mentioning
confidence: 99%
“…Mesozoic detrital zircons of the western mélange belt (Sauer et al, 2017), Late Jurassic Ingalls Ophiolite Complex of the Northwest Cascades system (NWCS) (Miller, 1985), the Late Cretaceous Nanaimo Group (Mustard, 1994;Matthews et al, 2017), the Okanogan Range batholith (Hurlow, 1993), and the Jurassic-Cretaceous strata of the Methow terrane (Surpless et al, 2014;Gordon et al, 2017) (Figs. 2, 43, and 44).…”
Section: Host Rockmentioning
confidence: 99%
“…The ~95 Ma grains are most likely derived from plutons in the Wenatchee block and from some plutons in the Chelan block (Table 3), whereas the smaller Early Cretaceous ~128-147 Ma cluster could have various potential sources (Table 4), including the Okanogan Range batholith (Hurlow, 1993), Northwest Cascades System (Brandon et al, 1988), and Methow terrane (Surpless et al, 2014(Surpless et al, , 2017. The ~147-197 Ma cluster may have multiple sources listed in Table 4, including the Ingalls Ophiolite Complex (Miller, 1985), Nanaimo Group (Mustard, 1994;Matthews et al, 2017), western mélange belt (Tabor et al, 2002), and the Methow terrane (Surpless et al, 2014;. The ~220 Ma grain, has potential sources in the Cascade River Schist-Holden unit, Little Jack unit, and reworked zircons from sedimentary rocks in the Ingalls Complex (Figs.…”
Section: Host Rockmentioning
confidence: 99%